Formulation of Sustained Release Zolpidem Tartrate Matrix Tablets Through Optimization and Their Evaluation - AHMED KHAN, MASHEER; CHATURVEDI, S.C. (Asian Journal of Chemistry, 2010)
The object of the present study is to develop sustained release system of the hypnotic agent zolpidem useful for the treatment of insomnia. Matrix tablet is the least complicated device to sustain the release of drug candidates. Two polymers HPMCK4M and HPMCK15M were selected to sustain the release up to 12 h. Optimization techniques using factorial design for two factors at three levels (32) was selected to optimize varied response variables viz., release rate exponent (n), t50 %, k, amount of drug released in 12 h and mean dissolution time. Software Zorel was used to calculate the release kinetics. The design expert software was used to generate ANOVA for selected five responses. The optimum formulations were selected and the results obtained with the experimental values were compared with the predicted values. Furthermore, the in vitro and in vivo studies were performed with newly formulated sustainedrelease zolpidem tablets and were compared with conventional marketed tablet (zoldem). In vivo investigation in rabbits showed sustainedrelease pharmacokinetic profile of zolpidem from the matrix tablets formulated using combination of HPMCK4M and HPMCK15M. In conclusion, the results suggest that the developed sustained-release matrix tablets could provide quite regulated release of zolpidem tartrate up to nearly 12 h.